September 2021 Placement Ads (The Accounting Review, 2021)
The deadline for free position ads to be included in this section of The Accounting Review is two months prior to the desired publication in the January, March, May, July, September, or November issues. Position ads, which are free with the purchase of a job posting in the AAA Career Center, should provide all relevant information about the available positions and must include contact information or application instructions for interested candidates. For more information on how to purchase a job posting in the Career Center, or for updated, detailed information about the placement listings in this issue, please go to the AAA website at http://aaahq.org and click on “Career Center,” or call our office at 941-921-7747.FUDAN UNIVERSITY, School of Management, Accounting Department invites applications for multiple positions in accounting for appointments beginning September 2022 (flexible). The ranks of Assistant Professor, Associate Professor, and Full Professor are open. We offer competitive salary, research fund, and housing allowance, commensurate with qualifications and experience. Review of applications will begin immediately and continue until the position is filled. Interested candidates will submit an electronic application package with the subject heading “Fudan Accounting Faculty Application 2021” to: hrfdms@fudan.edu.cn. The required application materials are cover letter, curriculum vitae, and samples of published or working papers. Relevant evidence of teaching effectiveness will be a plus if available.Three letters of recommendation can be sent later in separate emails directly to: hrfdms@fudan.edu.cn. Contact Information: Ms. Yan Zhou, Faculty Development Office,School of Management, 670 Guo Shun Road, Shanghai 200433; Phone: 86-21-25011470; Email: hrfdms@fudan.edu.cn. Visit: https://www.fdsm.fudan.edu.cn/AboutUs/index.aspxSTANFORD UNIVERSITY, Graduate School of Business invites applications for tenured and non-tenured faculty positions in accounting, beginning September 1, 2022, from candidates at all levels and stages of their careers who are interested in financial accounting, managerial accounting, tax, and other areas. Candidates should have or expect to complete a Ph.D. by September 1, 2022 and should possess a strong and active research record. The successful candidate will be expected to conduct research and to teach both M.B.A. and Ph.D. courses in accounting. Applicants should submit their applications electronically by visiting the website: https://www.gsb.stanford.edu/jobs/faculty-recruiting/, and uploading their curriculum vitae, research papers and publications, and teaching evaluations, if applicable. For an application to be considered complete, all applicants must submit a cv, a job market paper, and arrange for three letters of recommendation to be submitted. The application deadline is November 15, 2021, but candidates are strongly encouraged to submit as soon as possible. For questions regarding the application process, please send an email to: Faculty_Recruiter@gsb.stanford.edu. All qualified applicants will receive consideration for employment without regard to race, color, religion, sex, sexual orientation, gender identity, national origin, disability, protected veteran status, or any other characteristic protected by law. Stanford welcomes applications from all who would bring additional dimensions to the University's research, teaching, and clinical missions. Stanford is an Equal Employment Opportunity/Affirmative Action Employer.CALIFORNIA STATE UNIVERSITY, Stanislaus, Department of Accounting and Finance seeks a tenure-track Assistant Professor to teach Accounting. Candidates must possess a doctoral degree in Business Administration with an emphasis in Accounting from an AACSB-accredited doctoral institution at the time of appointment. Applicants must be able to demonstrate a commitment to teaching excellence as evidenced by strong teaching evaluations by students. Applicants should also provide evidence of experience or interest in serving a highly diverse, majority-minority student population. Ability and experience in teaching a variety of Accounting courses—particularly including Auditing and Intermediate Accounting—is preferred. Interest in Advanced Accounting and Data Analytics is a plus. Candidates who demonstrate the potential to publish in refereed journals appropriate to the field of Accounting through a record of published work will be preferred. Professional certifications and/or professional experience are a plus. For a complete job description and to apply, go to: https://careers.csustan.edu/st/en-us/job/499470/assistant-professor-of-accounting/. Contact information: Dr. Kim Tan, Chair, Department of Accounting and Finance, College of Business Administration, California State University, Stanislaus, One University Circle,, Turlock, CA 95382, USA' Email: KTan@csustan.edu. The position will remain open until filled. The appointment begins Fall 2022.CENTRAL MICHIGAN UNIVERSITY, College of Business Administration is accepting applications for a tenure-track accounting position (open rank). The anticipated start date is August 22, 2022. Primary responsibilities include teaching undergraduate courses, engaging in quality scholarship, and contributing through service. All teaching and research areas will be considered with preference given to applicants having interest in tax. The position offers a competitive salary, reduced teaching assignments for up to three years, and traditional research support. Applicants must submit an online application to be considered for this position: https://www.jobs.cmich.edu/. Review of applications will begin immediately and continue until the position is filled. Priority consideration will be given to applications received by August 1, 2021. Inquiries may be sent to: Dr. Amy M. Swaney, swane1a@cmich.edu. CMU is an AA/EO institution, providing equal opportunity to all persons, including minorities, females, veterans, and individuals with disabilities (see https://www.cmich.edu/office_president/ocrie/Pages/default.aspx).BAYLOR UNIVERSITY, Department of Accounting and Business Law invites applications for an Assistant (tenure-track), Associate, or Full Professor position starting Fall 2022. We will consider candidates from diverse backgrounds to hire a qualified candidate who will help the Department model Christ's message of hope to all people and support developing initiatives that shape the accounting profession. This position seeks individuals willing to conduct high-quality academic research while also contributing to the teaching excellence associated with Baylor University. We welcome applicants from all areas of accounting, but individuals with experience in managerial accounting or accounting information systems are encouraged to apply. The position requires a Ph.D. or close to completion of the doctoral degree (ABD). Interested individuals should apply via Interfolio: https://apply.interfolio.com/88987/ and provide a cover letter, current cv, and a personal statement of Christian faith. For questions regarding the position, please contact Dr. Bradley Lail, Department Chair, Accounting & Business Law (Bradley_Lail@baylor.edu, 254-710-6468). For questions regarding the application process, please contact Marion Palomino, Office Manager (Marion_Palomino@baylor.edu, 254-710-6465).BAYLOR UNIVERSITY, Department of Accounting and Business Law invites applications for a Clinical Assistant Professor position starting Fall 2022. We seek to hire three qualified candidates from diverse backgrounds who will help the Department model Christ's message of hope to all people and support developing initiatives that shape the accounting profession. Experience in or with taxation, managerial accounting, data analytics, professional writing and research, or accounting information systems are encouraged to apply, but we welcome applicants from all areas of accounting. The position requires either a Ph.D. or a master's degree with three years of professional/educational experience. The primary role of clinical faculty is to support the teaching mission of the department and to provide meaningful connections to practicing professionals. Clinical faculty fulfill their role in one of two profiles: scholarship or professional. The scholarship track is one with a terminal degree focusing on scholarship in addition to their teaching responsibilities. The professional track is one with a master's degree and a portfolio of recent professional experience appropriate for the level of courses expected to teach. Interested individuals should apply via Interfolio: https://apply.interfolio.com/88987/. For questions, contact Dr. Bradley Lail (Bradley_Lail@baylor.edu).HAMPDEN-SYDNEY COLLEGE, Department of Economics and Business invites applications for a tenure-track appointment in the beginning August 2022. Candidates should be prepared to teach courses in managerial accounting, foundations of business, and an elective field such as financial statement analysis, real estate, corporate finance, and/or international business. Candidates must have a strong commitment to teaching and the potential for sustained scholarship. A Ph.D. in accounting, management, economics, or a related field is required. Submit letter of application, curriculum vitae, graduate transcripts, indications of teaching competence, and three letters of recommendation. Applications must be submitted to: Dr. Gregory Dempster, Search Committee Chair, via Interfolio: https://apply.interfolio.com/89920/. Review of applications will begin September 1, 2021. Hampden-Sydney College is a private liberal arts men's college with a commitment to excellence in undergraduate education. Learn more about Hampden-Sydney at: http://www.hsc.edu.CALIFORNIA STATE UNIVERSITY, EAST BAY invites applications for an assistant professor position in accounting to begin in Fall 2022. Duties include teaching undergraduate and/or graduate courses in financial accounting, managerial/cost accounting, data analytics, auditing, or taxation, conducting academic research in different areas of accounting, and providing service to the University. Applicants must (1) have an earned Ph.D. in Accounting or related field from an AACSB accredited institution no later than the effective date of the appointment with specialized preparation in one or more of the following areas: accounting, auditing, and taxation, or MS/MA in Taxation or JD/LLM (Taxation) and BA/BS/MA/MS in Accounting with high-level professional tax experience, (2) demonstrate a record of scholarly activities, (3) meet CSU East Bay, College of Business and Economics AACSB faculty qualification standards for Scholarly Academics (SA) (available online), (4) possess strong communication skills, and (5) demonstrate experience in teaching, mentoring, research, or community service that has prepared them to contribute to our commitment to diversity and excellence. Applicants with professional certifications (CPA, CMA, CIA, CFE, or CISA) and/or extensive work experience in accounting, auditing, or taxation are preferred. Review of applications will begin on August 16, 2021. Please submit the following via PageUp: https://careers.pageuppeople.com/873/eb/en-us/job/501508 (click “Apply Now”). Submit (1) a letter of application, which addresses the qualifications noted in the position announcement, (2) a complete and current vita, which includes the names, affiliations, and contact information of three professional references, as well as the relationship with the applicant, (3) graduate transcripts, (4) a teaching statement, (5) samples of teaching evaluation, (6) samples of major publications, and (7) three confidential letters of recommendation. Applicants must also submit a one-page diversity statement addressing how you engage a diverse student population in teaching, research, mentoring, and advising. For questions, send inquiries to: accounting.recruitment@csueastbay.edu.CALIFORNIA STATE UNIVERSITY, LOS ANGELES invites applications for a tenure-track position as Assistant Professor of Accounting. Minimum Qualifications: An earned doctorate (Ph.D. or DBA) in Accounting from an AACSB-accredited institution is required; however, applicants nearing completion of the doctorate (ABD) may be considered. For an appointment, the doctorate must be completed by the date of appointment (8/18/2022). Documented University-level teaching experience is required. Preferred Qualifications: Demonstrated expertise in teaching Information Systems, Data Analytics, and/or Forensic Accounting; Demonstrated experience teaching online classes; Evidence of publishing in scholarly journals; Evidence of CPA license or other professional license/certification; and Documented accounting or other relevant business experience. Go to: https://www.calstatela.edu/FacultyAffairs/tenure-track-faculty-positionsMIDWESTERN STATE UNIVERSITY, Dillard College of Business Administration (AACSB accredited), Wichita Falls, TX, is seeking an Accounting Department Chair beginning Fall 2022. MSU is a 6,000-student, COPLAC-member regional university about 125 miles northwest of Dallas. The department's 11 full-time faculty members teach courses at undergraduate and graduate levels. Duties include overseeing and developing faculty, curriculum development and scheduling, and resolving student issues. This is a 9-month, tenure-track position that is normally filled by an Associate or Full Professor. The successful candidate will teach a 2-2 load of face-to-face and online courses with possible summer teaching. A Ph.D. in Accounting or related discipline awarded by an AACSB-accredited university, a track record of excellent in teaching, and demonstrated research and other intellectual contributions are required. A background in petroleum accounting is desired. To apply, please email a letter of application, cv, unofficial undergraduate and graduate transcripts, and three professional references to: lin.wang@msutexas.edu. Salary is competitive.WASHINGTON AND LEE UNIVERSITY invites applications for up to two tenure-track positions in Accounting at the rank of Assistant or Associate Professor (without tenure). We welcome applications from all fields and are particularly interested in candidates with teaching interests in financial accounting and/or taxation. The appointment begins July 1, 2022. Applicants should have a doctorate (or be close to completion) in Accounting or a related field from an AACSB accredited business school. Washington and Lee University promotes a dynamic and inclusive environment that allows students and employees of multiple backgrounds, cultures, and perspectives to learn, work, and thrive together. In keeping with the University Strategic Plan, we welcome applications from underrepresented minority candidates and members of other communities that are traditionally underrepresented in academia. For a complete position description and information on how to apply, visit the Interfolio portal: https://apply.interfolio.com/90314/. Contact accounting@wlu.edu with any questions.IDAHO STATE UNIVERSITY, Department of Accounting has a tenure-track faculty position at the rank of Assistant or Associate Professor available beginning Spring or Fall 2022. Begin or continue your career with a collegial and supportive department and college. Visit: https://isu.csod.com/ats/careersite/JobDetails.aspx?site=1&id=1319